Post-traumatic stress disorder and its associated factors among school-going children exposed to a tsunami disaster in Malaysia - Idayu Badilla, Idris; Aniza, Ismail; Rozita, Hod (Malaysian Public Health Physicians Associaton, 2015)
Posttraumatic stress disorder (PTSD) is a psychiatric diagnosis made when someone including children who experiences traumatic stressor. Those who are exposed to a more severe trauma have highest level of PTSD. The aim of this study was to measure the prevalence of PTSD and its associated factors among 219 children who were affected by a form of natural disaster which is the tsunami waves in a rural area in Malaysia. A cross sectional study was carried out among children aged 10-12 years 6 months after the traumatic event. Child Posttraumatic Stress Disorder –Reaction Index (CPTSD-RI) was used as a screening instrument which was answered by the affected children through a self-administered questionnaire. Forty six percent of these children had PTSD symptoms; 31.1% of these children had mild, 11.4% had moderate, 3.7% had severe PTSD and none had very severe PTSD. Result also showed that 91.8% had re-experiencing symptoms, 28.3% had numbing/avoidance symptoms and 49.3% had hyperarousal symptoms. Children with low social support (Adj OR = 2.3 (95% CI: = 1.3- 4.2)), and children who experienced deaths among someone close to them (Adj OR = 3.7 (95% CI =1.2 - 11.5)) were more likely to have symptoms of PTSD. This showed that children are at higher risk of developing PTSD as early as 6 months after the event and thus early intervention should be offered to them. Future longitudinal study can be carried out among affected children to assess whether these PTSD symptoms persist over time.